2021
DOI: 10.1007/s40122-021-00296-3
|View full text |Cite
|
Sign up to set email alerts
|

Headache Attributed to Vaccination Against COVID-19 (Coronavirus SARS-CoV-2) with the ChAdOx1 nCoV-19 (AZD1222) Vaccine: A Multicenter Observational Cohort Study

Abstract: Introduction The most frequently reported neurological adverse event of ChAdOx1 nCoV-19 (AZD1222) vaccine is headache in 57.5%. Several cases of cerebral venous thrombosis (CVT) have developed after vaccination. Headache is the leading symptom of CVT. For the differential diagnosis of headaches attributed to this vaccine and headaches attributed to CVT, it is of central clinical importance whether and, if so, how the phenotypes and course of these headaches can be differentiated. The study aims to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
3
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(72 citation statements)
references
References 37 publications
4
53
3
12
Order By: Relevance
“…Finally, with regard to the features of headache occurring after SARS-CoV-2 vaccines, some inputs were available in four different studies [15,53,120,121], and the main characteristics were described in Table 5. In synthesis, such headaches generally onset within the first day from injection and its duration is below 24 h. It is bilateral in 70-75% of the cases, and pulsating quality is reported by 30-40% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, with regard to the features of headache occurring after SARS-CoV-2 vaccines, some inputs were available in four different studies [15,53,120,121], and the main characteristics were described in Table 5. In synthesis, such headaches generally onset within the first day from injection and its duration is below 24 h. It is bilateral in 70-75% of the cases, and pulsating quality is reported by 30-40% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to treatment for post-vaccination headache, available literature provides little information. The aforementioned studies [15,53,120,121] show that the majority of patients had used analgesics to treat it, but distinction between patients with and without preexisting headache is not reported. Partial or complete response was reported by 97% of patients who took analgesics in the study of Ekizoglu [120], whereas in the two studies of Göbel and colleagues [53,121] it was shown that the two most commonly used drugs were paracetamol and ibuprofen (respectively used by 45.5% and 36% of subjects), whereas the one perceived being the most effective, by 46.2% of users, was acetylsalicylic acid.…”
Section: Discussionmentioning
confidence: 99%
“…After the second dose IFN-γ, CXCL-10, IL-15 and IL-6 were elevated to levels several times higher than after the first dose. This pattern is mirrored by headache, which usually occurs within the first 24 hours, remits after a couple of days after the first vaccination [89][90][91][92], and is more prevalent after the second dose [4]. As a side issue, it should be mentioned that CCL-2 and IL-3 were not significantly increased throughout the study, TNF concentrations were only slightly higher, and type I and III IFNs were not analysed at all in this study [96].…”
Section: Post-vaccination Headachementioning
confidence: 62%
“…Patterns similar to COVID-19 can be observed in cases of vaccine-related headache. Headache occurs early after vaccination [89][90][91][92] and is often accompanied by other systemic symptoms (i.e. myalgia and fever [91]).…”
Section: Post-vaccination Headachementioning
confidence: 99%
“…Notably, headache is the commonly reported from COVID-19 vaccine recipients [ 13 , 14 ]. Previous study reported headache started at 14.5 ± 21.6 h after received ChAdOx1 nCoV-19 vaccination and persisted for 16.3 ± 30.4 h and commonly located at forehead with dull aching in character [ 15 ]. Similarly, with BNT162b2 mRNA COVID-19 vaccine, headache begun 18 ± 27 h after vaccination, lasted for 14.2 ± 21.3 h,and most common located at forehead with pressing pain in character [ 16 ].…”
Section: Discussionmentioning
confidence: 99%